The Uses and Gratifications of Social Audio-Focused Apps: A Case Study of the Clubhouse Application - Younes, Dalia Abdelhamid (AUC Knowledge Fountain, 2024)
Social audio has recently emerged recently as a new form of social media based on voice. It spread rapidly through the Clubhouse application, which became a significant trend during the COVID-19 pandemic. The study aims to explore Egyptian content creators' motivations to join Clubhouse, study their motivations to produce their content, and identify the gratifications obtained from using this application. It also seeks to investigate the application`s sustainability within the Egyptian context by outlining the challenges faced by the Egyptian content creators. The study employs the uses and gratifications theory, conducting in-depth interviews with 17 Egyptian content creators. The findings reveal that the motivations of Egyptian content creators to join the Clubhouse application are to socialize with other people, particularly during COVID-19, and to satisfy their curiosity. Social responsibility, encouragement from friends, and managing discussions according to their own rules emerged as the key motivations for content creators to produce their content. The gratifications obtained include networking/building connections, self-development, personal branding, opening opportunities, freedom of expression, and keeping up with current affairs. Furthermore, the gratifications related to the technical features are audio superiority, convenience utility, easy usability, good audio quality, and documentation. The challenges identified include theft and fake profiles, cyberbullying, addiction, and ineffective moderation. Additionally, the recent update leads to limited accessibility and reach, and less privacy. The findings revealed that the application's sustainability within the context of Egypt is conditioned by addressing these challenges in addition to ensuring freedom of expression, and establishing a self-sustaining business.